THE ROLE OF FISH POND FARMING BUSINESS IN IMPROVING THE WELFARE OF FISH POND FARMERS IN PETELUAN INDAH VILLAGE, LINGSAR DISTRICT, WEST LOMBOK REGENCY - Yahya, Alfironi; Alwi, Muhammad; Astuti, Endang (Laboratorium Riset Ekonomi, 2025)
This study aims to analyze the role of fish pond farming in improving the welfare of fish pond farmers in Peteluan Indah Village, Lingsar District, West Lombok Regency. Fish pond farming is one of the rapidly growing local economic sectors with great potential to increase community income. The research method used is a qualitative approach with data collection techniques including interviews, observations, and documentation. The results of the study show that fish pond farming not only contributes to increasing farmers’ income but also encourages the creation of job opportunities, improvement of housing conditions, and better access to education and healthcare services. In addition, support from the government and local institutions further strengthens the sustainability of fish pond farming. Therefore, fish pond farming plays an important role in improving the living standards and welfare of pond farmers in the region.